Presence of Journalism research in books (1889-2012), and articles in Spanish Communication Journals (1980-2012) - de Lorenzo Rodríguez, Ignacio; López Pan, Fernando (Estudios sobre el Mensaje Periodístico, 2017)
Martínez Albertos proposed in 1976 the term of Journalistic Writing (Redacción Periodística) for the academic reflections on the practice of Journalism. Since then, several Spanish authors have been concerned about the metadisciplinary issues in this academic field. Despite their differences, even the most critical ones among them accept the existence of a discipline that studies Journalism with a peculiar approach. This article, which chooses the name Periodística to designate the discipline, studies comprehensively and systematically the research in Journalism published between 1989 and 2012 in the main Spanish Communication Journals. The results, which are collected in a database, support that, beyond theoretical approaches, there is a wide and proportionately significant research in Periodística that justifies its academic recognition.
Keywords: Journalism studies; Journalism research; Spanish Journals of Communication; metadisciplinarity.